Influence of Growth Regulators on Yield and Economics of Custard Apple (Annona squamosa L.) Cv. Balanagar - Thorat, U. K.; Dheware, R. M.; Jadhav, A. R. (International Journal of Economic Plants, 2018)
The field study was conducted on a well-established custard apple orchard of eight years age at Custard Apple Research Station, Ambajogai, Dist. Beed, during 2016-17, to study the influence of growth regulators on yield and economics of custard apple (Annona squamosa L.) Cv. Balanagar. The experiment framed was concentrated to find out effective concentration of GA3 and NAA as well as their combination for getting high yield of custard apple fruits. In present study, it had been observed that the foliar application of growth regulators was found beneficial for increasing yield of custard apple fruits. While, the combine spraying of GA3 25 + NAA 10 ppm twice i.e. before flowering (second fortnight of may) and one month after the first spray is beneficial for getting higher fruit yield of custard apple cv. ‘Balanagar’ under Marathwada region of Maharashtra.